Kondisi Optimum pH Larutan dan Kecepatan Pengadukan dalam Mengidentifikasi Mikroplastik Jenis PET Menggunakan Kitosan dari Cangkang Kepiting (Scylla serrata) - Nurila Rati; Indang Dewata (MASALIQ, 2025)
This study aims to determine the optimal pH and stirring speed for the identification and removal of polyethylene terephthalate (PET) microplastics using chitosan extracted from crab shell waste (Scylla serrata) through the coagulation method. The chitosan extraction process involved demineralization, deproteinization, and deacetylation stages. Subsequently, the extracted chitosan was applied as a coagulant in a solution containing PET microplastics under various pH levels and stirring speeds. The results indicate that chitosan derived from crab shell waste is effective in reducing microplastic concentrations, achieving a removal efficiency of 97.30% under optimal conditions of pH 6 and a stirring speed of 250 rpm. These findings highlight the significant potential of utilizing marine waste as an eco-friendly natural biopolymer in microplastic wastewater treatment. This research contributes to the advancement of sustainable biopolymer-based waste treatment technologies and supports efforts to mitigate microplastic pollution in aquatic environments.